2010
DOI: 10.1039/c0dt00540a
|View full text |Cite
|
Sign up to set email alerts
|

Cross coupling reactions of polyfluoroarenes via C–F activation

Abstract: This Perspective provides an overview of transition metal-catalyzed cross coupling reactions of polyfluoroarenes. When appropriate, stoichiometric C-F activation and subsequent reaction are briefly covered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(73 citation statements)
references
References 90 publications
0
73
0
Order By: Relevance
“…Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise . However, catalytic C-F bond functionalization reactions of highly fluorinated aromatic precursors via cross coupling reactions are still rare [4,14,17,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise . However, catalytic C-F bond functionalization reactions of highly fluorinated aromatic precursors via cross coupling reactions are still rare [4,14,17,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Braun has successfully carried out nickelcatalyzed Stille 7,8 and Suzuki 9 coupling reactions of several perfluoroheteroaromatic derivatives, pentafluoropyridine and 2,4,6-trifluoro-5-chloropyrimidine, respectively. Radius has also reported similar Suzuki cross -coupling reactions between octafluorotoluene and decafluorobiphenyl and various electron rich aryl boronic acid derivatives in which the C-F bond para to the trifluoromethyl or pentafluorophenyl group was activated and fluorine displaced by an aryl group.…”
Section: Introductionmentioning
confidence: 99%
“…So, the selective cleavage of one or several C-F bonds in those molecules followed by a suitable functionalization is a way to obtain partially fluorinated compounds of high interest. Reviews with an extensive coverage of the subjects of C-F activation, 6,7,[224][225][226] and fluorination 10,227,228 are available in the literature. The purpose of this section is to cover palladium mediated processes in the area.…”
Section: C-f Activation and Fluorinationmentioning
confidence: 99%